One last scream - O'Brien, Kevin, 1955- (Pinnacle fiction, 2008)
Over the last eleven years, twelve women have vanished without a trace, and a troubled woman who suffers from blackouts holds the key to solving a new series of murders when she becomes part of a serial killer's deadly game.